Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1152/japplphysiol.00329.2012
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity typical of mountain climbing does not exacerbate acute mountain sickness in normobaric hypoxia

Abstract: Physical exertion is thought to exacerbate acute mountain sickness (AMS). In this prospective, randomized, crossover trial, we investigated whether moderate exercise worsens AMS in normobaric hypoxia (12% oxygen, equivalent to 4,500 m). Sixteen subjects were exposed to altitude twice: once with exercise [3 × 45 min within the first 4 h on a bicycle ergometer at 50% of their altitude-specific maximal workload (maximal oxygen uptake)], and once without. AMS was evaluated by the Lake Louise score and the AMS-C sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…People aged >40-60 years tend to develop AMS less than younger adults [27]. Recent studies examining the hypothesis that exercise enhances AMS yielded controversial results [29][30][31].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…People aged >40-60 years tend to develop AMS less than younger adults [27]. Recent studies examining the hypothesis that exercise enhances AMS yielded controversial results [29][30][31].…”
Section: Epidemiologymentioning
confidence: 99%
“…Avoiding overexertion following ascent is another commonly recommended measure, although studies have reported varying results about the relationship between exertion and risk of AMS [29,30,113]. Abrupt cessation of caffeine intake in chronic users of caffeinated beverages may provoke withdrawal symptoms that mimic those of AMS [114].…”
Section: Other Measuresmentioning
confidence: 99%
“…The higher expression of adhesion molecules observed in both capillary-drawn samples (Fig. 1) may also suggest that the routinely used methods adopted in this research to increase blood flow to these sampling sites, either via action of nonivamide and butoxyethyl nicotinate containing cream-Finalgon ® (Zavorsky et al 2005;Schommer et al 2012;Beneke and Alkhatib 2015) or submersion of limb in hot water, may have contributed to neutrophil activation. Nonivamide has been described to, when applied to the skin, induce release of vasodilative polypeptides such as calcitonin-gene-related peptide (CGRP) and substance P (Stucker et al 1999).…”
Section: Discussionmentioning
confidence: 89%
“…Also, it should be considered that the study hypothesis was based on observation of AMS symptoms developed when hypoxic exposure is combined with moderate (Roach et al, 2000) and intense (Wu et al, 2012) exercise at altitude. However, mild to moderate intensity exercise apparently does not worsen AMS (Schommer et al, 2012;Rupp et al, 2013). In the present study, a 30 min high-intensity exercise protocol was applied.…”
Section: Limitationsmentioning
confidence: 99%
“…Less than 1 h of hypoxic exposure can increase cerebral blood volume by 2 mL and brain parenchyma volume by 8 mL in a resting person (Dubowitz et al, 2009). Symptoms of AMS are more severe when hypoxic exposure is combined with exercise (Roach et al, 2000) and seems to be more frequent when intense (Wu et al, 2012) rather than moderate physical activity (Schommer et al, 2012) is carried out at altitude. Thus, even brief intense exercise in hypoxia may provoke the initial events that eventually lead to AMS.…”
Section: Introductionmentioning
confidence: 99%